A Spatial Analysis of the Italian Second Republic - LANDI, Massimiliano (Institutional Knowledge at Singapore Management University, 2013)
The Optimal Classification method is applied to a newly created data set to provide a spatial map of the Italian Second Republic (1996–2008). A bi-dimensional political space was found in the XIII Legislature and virtually a one-dimensional political space in the XIV and XV Legislatures. In addition, the main dimension is explained along the government–opposition dimension rather than on the traditional left–right dimension. During the Second Republic, Italy experienced changes in the electoral system and in the format of parties. The data are used to discuss the implications of either change on the dimensionality space. It was found that the format of the party system was a more important determinant of the dimensionality of the political space than changes in the electoral system.